Remdesivir triphosphate blocks DNA synthesis and increases exonucleolysis by the replicative mitochondrial DNA polymerase, Pol γ - Ciesielska, Elena J.; Kim, Shalom; Bisimwa, Hyacintha-ghislaine M.; Grier, Cody; Rahman, Md. Mostafijur; Young, Carolyn K.J.; Young, Matthew J.; Oliveira, Marcos T. [UNESP]; Ciesielski, Grzegorz L. (Elsevier, 2021)
The COVID-19 pandemic prompted the FDA to authorize a new nucleoside analogue, remdesivir, for emergency use in affected individuals. We examined the effects of its active metabolite, remdesivir triphosphate (RTP), on the activity of the replicative mitochondrial DNA polymerase, Pol γ. We found that while RTP is not incorporated by Pol γ into a nascent DNA strand, it remains associated with the enzyme impeding its synthetic activity and stimulating exonucleolysis. In spite of that, we found no evidence for deleterious effects of remdesivir treatment on the integrity of the mitochondrial genome in human cells in culture.
Keywords: Antiviral nucleoside analogues; COVID-19; DNA polymerase gamma; Mitochondrial DNA; Remdesivir